Penerapan Pembelajaran Keterampilan Proses Untuk Meningkatkan Pemahaman Siswa SD Kelas IV Pada Materi Konsep Energi Bunyi - muslimin muslimin; Muhammad Amran (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2020)
The purpose of this research is to improve students' understanding of the concept of sound energy after learning by using a process skills approach. The data collection techniques of this study were tests, direct interviews, observations. Data analysis techniques with descriptive statistics to describe the level of student understanding. The results of the study are the use of the process skills approach in the fourth grade students of SD Inpres Maralleng can improve understanding in natural science subjects especially sound energy concept material.